Analisis Kesulitan Guru SD di Lombok Utara dalam Penyusunan Karya Ilmiah - Arif Widodo; Awal Nur Khalifatur Rosyidah; Ida Ermiana; Ashar Pajarungi Anar; Linda Feni Haryati; Setiani Novitasari (SAP (Susunan Artikel Pendidikan), 2021)
Professional teachers are not only required to teach well but also must possess good writing skills. Scientific work for teachers is part of professional development. However, not a few teachers still have difficulty writing scientific papers. This study intends to analyze the difficulties of teachers in compiling scientific papers. This research utilized descriptive quantitative. The research took place at SDN 1 and SDN 5 Pemenang Barat, North Lombok district. The research was conducted from August to September 2020. The number of teachers being the research sample was 20 teachers. Data collection used survey methods. The instruments were in the form of an open questionnaire and a closed questionnaire. The data analysis technique used descriptive statistics. The results showed that most teachers found it difficult to compile scientific papers. The contributing factors included lack of motivation, lack of understanding of the concept of scientific work, the feeling of not having time, and the low intensity of writing scientific papers.